Lysyl oxidase propeptide promotes adipogenesis through inhibition of FGF-2 signaling. (2nd January 2017) - Griner, John D.; Rogers, Carl J.; Zhu, Mei-Jun; Du, Min
ABSTRACT: Lysyl oxidase (LOX) catalyzes the oxidative deamination of lysine residues in collagen and elastin, key components of connective tissue. LOX is synthesized as an inactive 50 kD pre-proenzyme, and secreted to the extracellular matrix where it is cleaved into an active 32 kD LOX, and an 18kD free propeptide (LOX-PP), purportedly an inhibitor of fibroblast growth factor-2 (FGF-2) signaling. Given that adipocytes are distributed inside the connective tissue, it is likely that LOX-PP has an important regulatory role in adipogenesis, which has not been studied. Using NIH 3T3-L1 cells, we observed that FGF-2 inhibited adipogenesis, and LOX-PP promoted adipogenesis of 3T3-L1 cells in the presence of FGF-2; the expression of peroxisome proliferator-activated receptor (PPAR) γ and CCAAT-enhancer binding protein (C/EBP) α, two markers of adipogenesis, were enhanced in the presence of LOX-PP. We further observed that LOX-PP down-regulated AKT and ERK1/2, two proliferative signaling proteins down-stream of FGF-2 signaling. Similarly, inhibition of FGF-2 receptor signaling by canofin, a competitive inhibitor of FGF-2 receptor, promoted adipogenesis albeit less effective compared to LOX-PP. To further explore whether LOX-PP promoted adipogenesis through inhibition of FGF-2 signaling, site directed mutagenesis of LOX-PP, resulting in an Arg158 to Gln158 mutation which abolishes the inhibitory activity of LOX-PP to FGF-2 receptor, attenuated the adipogenic promoting properties of LOX-PP. In summary, for the first time, our data show that LOX-PP enhances adipogenesis at least partially through inhibition of FGF-2 receptor signaling. Our data suggest that LOX-PP may serve as a bona fide therapeutic target for regulating adipogenesis and adipose tissue development.